Diagnostic value of cholesterol in pleural fluid as a differential marker of effusions - Quispe-Aranda, David (2026)
Introduction: Pleural effusion is an abnormal accumulation of fluid in the pleural space, and its correct classification into exudates or transudates is essential for diagnosis and treatment. The Light criteria are the laboratory standard for this classification, although they have limitations. Cholesterol in pleural fluid has been proposed as an alternative marker that could improve diagnostic accuracy. Objective: To evaluate the diagnostic utility of cholesterol in pleural fluid as a differential marker between exudative and transudative pleural effusions. Methods: An observational, cross-sectional, analytical study was conducted, including 80 pleural fluid samples collected at the Emergency Center of Metropolitan Lima. Cholesterol concentrations were determined using the enzymatic colorimetric method CHOD-PAP-Trinder, previously validated for pleural fluid. The ROC curve was used to establish the optimal cutoff point, and the sensitivity and specificity of the marker were calculated. Results: The ROC analysis revealed an area under the curve (AUC) of 0.83. The optimal cutoff point was 32 mg/dL, with a sensitivity of 88% and specificity of 74.5%. Chronic kidney disease was the most common pathology associated with pleural effusion in the studied sample (45%). Conclusion: Cholesterol in pleural fluid, measured using a validated technique, demonstrated adequate diagnostic performance to differentiate between exudative and transudative pleural effusions, with high sensitivity. Its incorporation into routine biochemical analysis could improve diagnostic accuracy in cases where the Light criteria are inconclusive